Teaching Vocabulary Mastery through Word Wall Media (An Experimental Study at MTs DDI) - Erniwati, Erniwati; Mertosono, Sudarkam Ramlan; Wahyudin, Wahyudin; Fadilah, Fitria Nur (Institut Agama Islam Negeri Palopo, 2024)
This research aims to determine the effectiveness of using Word Wall media in improving vocabulary mastery of grade eight students of MTs DDI Lonja Sigi, Central Sulawesi. Â This is a quasi-experimental research design, involving 33 students selected through total population sampling technique. Â To collect the data, paper-and-pencil method with tests (pretest and posttest) was used. Result indicated that there was a significant difference between studentsâ€™ vocabulary mastery before and after the intervention. With Ï=0.05 and df=31, it was found that the tcounted value of 9.21 is higher than the tcritical value of 1.696. This means, the research hypothesis is accepted. In other words, using Word Wall media can improve vocabulary mastery of grade eight students of MTs DDI Lonja Sigi.Â Â